Consumer Acceptance and Willingness to Pay for Prebiotic Kuini Juice in Malaysia - Norzalila Kasron; Siti 'Aisyah Baharudin; Saiful Bahri Saari; Mohd Nur Hafiz Mat Azmin; Nor Azlina Saari (Universitas Ahmad Dahlan, 2021)
Changing consumers' lifestyles and food consumption patterns provide an excellent opportunity to develop the prebiotics market in Malaysia. Therefore, Malaysia is trying to improve products based on local ingredients such as kuini juice developed by the Malaysian Agricultural Research and Development Institute (MARDI). The high fibre content found in kuini makes it suitable to be used as one of the essential ingredients in prebiotic drinks. This research attempted to analyse consumer acceptance and willingness to pay for prebiotic kuini juice. A survey was conducted in Peninsular Malaysia, where 400 respondents were interviewed using a structured questionnaire. Exploratory factor analysis, Kaiser-Meyer-Olkin test and Bartlett's Test of Sphericity were utilised for objective analysis 1, while the Contingent Valuation Method was utilised for objective analysis 2. The result showed that 73% of respondents had taken prebiotic juice in the past. The tendency to choose prebiotic kuini juice by MARDI was 52% compared to existing products in the market. Significant findings determined consumers' preference factors, including product marketing and promotion, which influenced the purchasing of prebiotic kuini juice. The willingness to pay by respondents was lower at RM4.10/300ml bottle than the actual price bid at RM5.70/300ml bottle. As consumer awareness of health increases, it was an opportunity for the health food industry to expand the functional food market. However, some improvements should be adjusted to ensure prebiotic kuini juice can compete with other similar products in the market. Government support is needed to encourage indigenous fruits cultivation and to produce value-added products.